(3QSGdI aj GdHhGSjQs - (3GdbhUhfj , TeS GdOjf eMeO Hf eMeO Hf eMeO Hf HOQ GdOjf GdbhUhfj,J (B931 (3g` s
(3ChdgG (B:s
(3fMeOc Gddge jG MGaX GdUMI hHYO ajbhd GdYHO GdabjQ gPg QSGdI UMjMI dWjaI eMJhjI Ydi eHGMK TQjaI HGdYdI GdeYQhaI HGdHhGSjQ s
(3BNQgG (B:s
(3HRQ bWhfG hdYGH MH GdSaQ Ld hjbQU ef OQge Edi OQge hGdGSJYeGd hGMO YfO Gdfhe GfJgi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B260s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs